Public Perception of Women's Political Participation in the 2024 Legislative Election (Case Study of Dapil 2 and Dapil 4 in Palu City) - Reski Muliyana; Sitti Rabiatul Wahdaniah Herman; Muthia Muthia (ARISTO, 2026)
This study aims to analyze public perception of women's political participation in the 2024 legislative election in Palu City, focusing on two constituencies: Dapil 2 and Dapil 4. A qualitative descriptive approach was used, with data collected through in-depth interviews, observation, and literature studies. Thirty informants, including male and female voters, were purposively selected. The findings reveal that Dapil 2 holds a positive perception of female candidates due to their active engagement in social initiatives and structured campaigns, while Dapil 4 reflects a more negative perception due to low visibility and male dominance. Local socio-cultural factors significantly shape these perceptions. The study recommends inclusive campaign strategies and gender-based political education to enhance women's political participation at the local level. Keywords:  Political Participation; Woman; Public Perception; 2024 Election; Palu City